2016
DOI: 10.3892/or.2016.4857
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA decreases the protein expression of EGFR, and IGFR blocking the PI3K/Akt/mTOR pathway in gastric carcinoma AGS cells both in vitro and in vivo

Abstract: Tan-IIA exerts powerful inhibitory effects in gastric cancer AGS cells. The PI3K/AKT/mTOR pathway is one of the most frequently dysregulated kinase cascades in human cancer. In the present study, we investigated the protein expression levels of PI3K, AKT and mTOR in AGS cells treated with Tan-IIA both in vitro and in vivo. The AGS cells were treated with Tan-IIA for different durations in vitro. In the in vivo study, AGS cell xerograft SCID mice were treated with Tan-IIA for 8 weeks. Subsequently, the protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 23 publications
2
29
0
Order By: Relevance
“…Su et al [38] demonstrated that Tan IIA could inhibit the growth of gastric cancer AGS cells through blocking the PI3K/Akt/mTOR pathway and downregulating the expression of EGFR , and again this result was very similar to our results. Furthermore, we investigated the specific mechanism of Tan IIA inducing apoptosis of glioma cells, and found that Tan IIA could significantly inhibit the expression of Bcl-2 but promote the expression of Bax, which were both apoptosis-related proteins.…”
Section: Discussionsupporting
confidence: 82%
“…Su et al [38] demonstrated that Tan IIA could inhibit the growth of gastric cancer AGS cells through blocking the PI3K/Akt/mTOR pathway and downregulating the expression of EGFR , and again this result was very similar to our results. Furthermore, we investigated the specific mechanism of Tan IIA inducing apoptosis of glioma cells, and found that Tan IIA could significantly inhibit the expression of Bcl-2 but promote the expression of Bax, which were both apoptosis-related proteins.…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, inhibition of PI3K signalling is currently considered a very promising approach for treating these diseases and a principal target for drug development . The study reported that Tan IIA that is one of the compounds of Dan‐shen inhibited tumour growth in gastric carcinoma via downregulating the PI3K/Akt/mTOR in vitro and in vivo . However, it is not clear whether Tan‐Ⅰ affects PI3K/Akt/mTOR signalling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin (VIM) is a famous EMT marker that promotes tumor invasion and drug resistance in ovarian cancer, colon cancer, and gastric cancer [3234]. EGFR is also a famous oncogene in ovarian cancer, breast cancer, and gastric cancer [35–37]. Moreover, PTEN is a well-studied gene that inhibits tumor growth and invasion in nearly all types of human cancers, including gastric cancer, breast cancer, and lung cancer [3841].…”
Section: Discussionmentioning
confidence: 99%